Junior Farmer Field Schools, Agricultural Knowledge and Spillover Effects: Quasi-experimental Evidence from Northern Uganda - Jacopo Bonan; Laura Pagani (Fondazione Eni Enrico Mattei (FEEM), 2016)
We analyse the impact of a junior farmer field school project in Northern Uganda on students' agricultural knowledge and practices. We also test for the presence of intergenerational learning spillover within households. We use differences-in-differences estimators with ex-ante matching. We find that the program had positive effects on students' agricultural knowledge and adoption of good practices and that it produced some spillover effects in terms of improvements of household agricultural knowledge and food security. Overall, our results point to the importance of adapting the basic principles of farmer field schools to children.
Keywords: O13; O22; O55; C93; 330; Junior Farmer Field Schools; Agricultural Extension; Intergenerational Learning Spillover; Uganda